Epigenetic Mechanisms Shape the Biological Response to Trauma and Risk for PTSD: A Critical Review. (17th April 2013) - Heinzelmann, Morgan; Gill, Jessica
Abstract : Posttraumatic stress disorder (PTSD) develops in approximately one-quarter of trauma-exposed individuals, leading us and others to question the mechanisms underlying this heterogeneous response to trauma. We suggest that the reasons for the heterogeneity relate to a complex interaction between genes and the environment, shaping each individual's recovery trajectory based on both historical and trauma-specific variables. Epigenetic modifications provide a unique opportunity to elucidate how preexisting risk factors may contribute to PTSD risk through changes in the methylation of DNA. Preexisting risks for PTSD, including depression, stress, and trauma, result in differential DNA methylation of endocrine genes, which may then result in a different biological responses to trauma and subsequently a greater risk for PTSD onset. Although these relationships are complex and currently inadequately described, we provide a critical review of recent studies to examine how differences in genetic and proteomic biomarkers shape an individual's vulnerability to PTSD development, thereby contributing to a heterogeneous response to trauma.